O PERSONALISMO DE KAROL WOJTYÅA: Personalism of Karol Wojtyla - Damascena, Francisco Agamenilton (2020)
this article aims to present the personalism of Karol WojtyÅ‚a, using the analytical method and a bibliographical research. WojtyÅ‚a, through a creative synthesis between the philosophy of being and the philosophy of consciousness, offers an answer to the question "who is the human person". For this, he breaks the classic scheme of the "person to action" and he does the intellectual itinerary to the contrary: from action to person. He explains themes like suppositum, consciousness, being and action, freedom, truth. The conclusion is the overcoming of the rigidity and exteriority of the scholastic scheme in the understanding of human dynamism and a notion of the human person. Objectivity and subjectivity are considered as constitutive dimensions of the human being. This new understanding is important to rescuing and promoting the value of the human person in opposition to its reification.